The Will to Empower : Democratic Citizens and Other Subjects - Cruikshank, Barbara (Cornell paperbacks, 2019)
How do liberal democracies produce citizens who are capable of governing themselves? In considering this question, Barbara Cruikshank rethinks central topics in political theory, including the relationship between welfare and citizenship, democracy and despotism, and subjectivity and subjection. Drawing on theories of power and the creation of subjects, Cruikshank argues that individuals in a democracy are made into self-governing citizens through the small-scale and everyday practices of voluntary associations, reform movements, and social service programs. She argues that our empowerment is a measure of our subjection rather than of our autonomy from power. Through a close examination of several contemporary American "technologies of citizenship"--Welfare rights struggles to philanthropic self-help schemes to the organized promotion of self-esteem awareness-she demonstrates how social mobilization reshapes the political in ways largely unrecognized in democratic theory. Although the impact of a given reform movement may be minor, the techniques it develops for creating citizens far extend the reach of govermental authority. Combining a detailed knowledge of social policy and practice with insights from poststructural and feminist theory, The Will to Empower shows how democratic citizens and the political are continually recreated.